PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH PEMUKIMAN PADA KECAMATAN TUNGKAL ILIR KABUPATEN TANJUNG JABUNG BARAT (CIVIL SOCIETY PARTICIPATION IN HOUSEHOLD GARBAGE MANAGEMENT AT TUNGKAL ILIR SUBDISTRICT WEST TANJUNG JABUNG REGENCY) - Fitriza Yulian (Inovasi, 2017)
The aim of this research is to identify the influencing factors of civil society participation in household garbage management, to identify level of society participation in household garbage management and to analyse the characteristic of relation of society characteristic and settlement environment with society participation level in household garbage management till cleanliness and continuity of settlement environmental beauty at Tungkal Ilir subdistrict. In result of distribution frequency anlaysis stated factors that influence society participation level in household garbage management at Tungkal Ilir subdistrict are education level, earning, yard, environment circumstance, attitude to environment and society perception. Level of society participation in household garbage management in Tungkal Ilir subdistrict West Tanjung Jabung categorized low or less that equal to 56,0%, medium or enough equal to 25,0 % and high or good equal to 19,0%. Based on chi-square analysis result, society and environment characteristic correlate positive and very real with society participation level in household garbage management at Tungkal Ilir subdistric West Tanjung Jabung, society characteristic which has no relationship with society participation level in household garbage management is time of stay periode. Keywords: house waste management, society characteristic, society participation